Pemberdayaan UMKM melalui Sosialisasi NIB dan Sertifikasi Halal di Desa Bendungan - Solichah, Mar’atus; Laili, Innayatul; Rohimah, Nur; Masyitho, Sinta Yuliani; Ariba, Sania Rosya (Irajagaddhita, 2025)
Program pemberdayaan Usaha Mikro, Kecil, dan Menengah (UMKM) memiliki The empowerment of Micro, Small, and Medium Enterprises (MSMEs) plays a crucial role in enhancing competitiveness and community welfare. However, many MSME actors still face challenges related to business legality and product quality standards, particularly regarding the Business Identification Number (NIB) and halal certification. The Community Service Program (KKN) in Bendungan Village, Kraton District, aimed to provide socialization on the importance of NIB and halal certification as efforts to strengthen legality, consumer trust, and market access. The implementation methods included counseling, interactive discussions, and simple technical assistance involving local MSME actors, especially bag and wallet craftsmen. The results indicated an increase in participants’ understanding of the procedures for obtaining NIB and the benefits of halal certification in improving product marketability. Furthermore, the community became more aware of the urgency of business legality in expanding marketing networks, both offline and digital. Thus, this socialization program makes a tangible contribution to enhancing the capacity of MSME actors towards more professional, competitive, and sustainable businesses.